Liquid-Phase Hydrogenation of Citral Over Pt/TiO2 and Pt-Fe/TiO2 Catalysts - Ananthan, S.A.; Narayanan, V. (Asian Journal of Chemistry, 2010)
The liquid phase hydrogenation of citral to unsaturated alcohol over supported platinum catalysts has been studied. The catalysts were used Pt/TiO2 reduced at low or high temperature and the bimetallic Pt-Fe/TiO2 low or high temperature catalysts. As solvent n-heptane, an equimolar mixture n-heptane-1-propanol and 1-propanol were used. The reactions were carried out at a hydrogen pressure of 8.27 bar at 363 K. In the low temperature catalyst, the catalytic activity increases upon the addition of Fe3+. This positive effect was obtained keeping constant the selectivity to the unsaturated alcohol, being high selective to the products obtained by hydrogenation of the C=O bond. In the high temperature catalysts, both the addition of Fe and the presence of TiO2 moieties generated by the strong metal support interaction (SMSI) effect, lead to an increase of surface acidity. In low or high temperature catalysts, an increase in the polarity of the solvent increases the catalytic activity. However the reaction pathway is modified by the presence of acid sites which in polar solvents allow the formation of acetals, mainly in the high temperature catalysts.